2D multichannel seismic reflection processed data (GI Gun working area dataset) of RV MARIA S. MERIAN during cruise MSM98/2, Norwegian Sea - Rachel Barrett; Jens Schneider von Deimling; Henrik Grob; Kai-Frederik Lenz; Arne Lohrberg; Sebastian Krastel (PANGAEA, 2025)
This dataset contains twenty-three (23) high-resolution multi-channel seismic reflection (MCS) profiles collected from the Norwegian Sea and presented in the corresponding publication. The data were acquired during expedition MSM98/2 in January/February 2021 and were processed using a standard processing flow with particular focus on resolving deposits that terminate at the landslide headwall imaged in the data. The processing flow involved the application of geometry, band-pass filtering (20-35-350-490 Hz) and scaling, followed by FK-filtering, deconvolution, correction for spherical divergence, and trace editing to remove low quality channels and shots. The data were then corrected for normal move-out using constant velocity, and a burst-noise median filter (THOR) was applied before CMP stacking (with a CMP spacing of 7.5 m) and post-stack finite difference (FD) migration.